2021
DOI: 10.1002/er.7430
|View full text |Cite
|
Sign up to set email alerts
|

A facile one‐step synthesis of bio‐inspired porous graphitic carbon sheets for improved lithium‐sulfur battery performance

Abstract: The development of cost-effective carbon materials with tunable porosity for energy storage applications is challenging. In this study, a facile one-step in situ chemical activation process was adopted to synthesize porous graphitic carbon sheets (GCSs) from a tissue paper. The resulting GCS exhibits high specific surface area, large pore volume, and a highly graphitized carbon structure with graphene-like morphology. Sulfur-infused GCSs with optimum sulfur loading along with GCS-coated separator deliver a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…The sp 2 hybridized graphitic layers and tangential vibration of carbon atoms symbolic of their degree of graphitization and conductivity is indicated by the G‐band. [ 3 ] In contrast, the D‐band is representative of the defects in the edge planes and graphitic layers. It can be observed from Figure 2b, that an improvement in the number of sp 2 hybridized carbon atoms is exhibited by the reduction in D‐band and enhancement in G‐band intensity after activation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sp 2 hybridized graphitic layers and tangential vibration of carbon atoms symbolic of their degree of graphitization and conductivity is indicated by the G‐band. [ 3 ] In contrast, the D‐band is representative of the defects in the edge planes and graphitic layers. It can be observed from Figure 2b, that an improvement in the number of sp 2 hybridized carbon atoms is exhibited by the reduction in D‐band and enhancement in G‐band intensity after activation.…”
Section: Resultsmentioning
confidence: 99%
“…[1] Nevertheless, the low energy density (<10 Wh kg −1 ) restricts their individual commercialization. [3] materials leads to the rationale understanding that the energy and power densities of LIHCs mainly depend on the cathode counterparts due to the asymmetric device fabrication and huge difference in the ratio of specific capacity of cathode:anode. [1] In this context, different types of carbon materials have been extensively studied as cathode materials for LIHCs due to their high conductivity, ease of availability, tunable physical and chemical properties, and high economic value.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…have been converted into BDC with the micro–mesoporous structure for LSBs (Table 1). For example, Harimohan et al 119 adopted tissue papers as a precursor to obtain porous graphitic carbon sheets. The composite cathode exhibited highly reversible and stable electrochemical performance.…”
Section: Natural Porous Bdc-based Hostsmentioning
confidence: 99%
“…They found that such anode shows excellent electrochemical properties compared to commercial graphite. Additionally, Harimohan et al 20 used a chemical activation method to synthesize porous carbon sheets from tissue paper. They discovered that the new sheets display higher specific surface area and large pore volume.…”
Section: Introductionmentioning
confidence: 99%